(untitled) (Signifikan: Jurnal Ilmu Ekonomi, 2021)
Retail sukuk is a sharia product offered to Indonesian citizens as a safe and profitable investment instrument. This study identified the strengths, weaknesses, opportunities, and threats that the government may face in offering retail sovereign sukuk. It aimed to provide the government the appropriate strategies based on the historical data of listed retail sukuk and its peripherals during 2009-2020. This paper used a qualitative research approach. The data collection techniques used were literature review and in-depth interview. Internal and external factors were identified. SWOT matrix was made prior to analysis. The results show that the coupon rate offered by retail sovereign sukuk is mostly higher than BI rate. Market expansion is needed. The government shall optimize all distribution partners. Newly innovated products should be developed. Certain criteria should be formulated to determine coupon rate. This research suggests that an independent Special Purpose Vehicle should be reconstructed as a separate entity. JEL Classification: E62, G23, G28, H63 How to Cite: Muchtar, M. (2021). Opportunities and Challenges of Retail Sovereign Sukuk Issuance: Lessons from Twelve Years’ Experience. Signifikan: Jurnal Ilmu Ekonomi, 10(2), 259-274. https://doi.org/10.15408/sjie.v10i2.20093.